Towards a preferred housing environment: examining satisfaction elements outside a dwelling unit among Ahmadu Bello University (Kongo Campus) staff, Nigeria - Bello, Ashiru; Dola, Kamariah; Shaba, Suleiman A. (Faculty of Design & Architecture, Universiti Putra Malaysia, 2014)
In this paper, we built upon findings from a housing satisfaction study (considering largely those elements which are external to the dwelling unit) among two categories of university staff (academic and non-academic). Responses are gathered from university owned housing developments at four (4) different locations as well as private accommodations. 224 households (that is 20% of the entire staff population as at July 2011) were studied by selecting one out of five houses in each of the identified clusters. The study found that, the macro environmental effects of safety and security positively affects occupants’ overall satisfaction. However, although soft exterior landscaping is found to be generally poor in all the studied housing developments, it has no effect on the overall satisfaction. The scenario reflects the contextual level of socio-economic development; hence the study highlights the need to emphasize basic elements, particularly in response to the growing interest in fostering sustainable development through reduced material consumption.